Enhanced Interfacial Contact and Lithium-Ion Transport in Ionic Liquid Polymer Electrolyte via In-Situ Electrolyte-Cathode Integration - Zehua Chen; Mianrui Li; Shengguang Qi; Li Du (Molecules)
Solid polymer electrolytes (SPEs) have attracted much attention due to their excellent flexibility, strong interfacial adhesion, and good processibility. However, the poor interfacial contact between the separate solid polymer electrolytes and electrodes leads to large interfacial impedance and, thus, hinders Li transport. In this work, an ionic liquid-modified comb-like crosslinked network composite solid-state electrolyte with an integrated electrolyte/cathode structure is prepared by in situ ultraviolet (UV) photopolymerization. Combining the enhanced interfacial contact and the introduction of ionic liquid, a continuous and fast Li+ transport channel at the electrolyte–cathode interface is established, ultimately enhancing the overall performance of solid-state lithium batteries. The composite solid electrolytes (CSEs) exhibit an ionic conductivity of 0.44 mS cm−1 at 60 °C. LiFePO4//Li cells deliver a high discharge capacity (154 mAh g−1 at 0.5 C) and cycling stability (with a retention rate of more than 80% at 0.5 C after 200 cycles) at 60 °C.